A Survey for Informed Consent Before Surgery - Beyaztaş, Fatma Yücel; Demirkan, Özgür (The Bulletin of Legal Medicine, 2001)
Between 20 March-01 May 2001, the operated patients in General Surgery Departments of the Social Insurance Society, State and University hospitals in Sivas were applied the poll for evaluation of informed consent pre-operation. 89 cases in Social Insurance Society hospital, 96 cases in University hospital, 167 cases in State hospital of total 352 cases were applied the poll questions face to face. 44 (12.5 %) cases, most of which were younger than 18 old years or emergency cases, were not taken informed consent pre-operation. 23 (52.3 %) cases of these ones were from University hospital. All cases in Social Insurance Society hospital were taken consent pre-operation. 5.2 % of the cases in University hospital, 7.2 % of the cases in State hospital were not taken consent pre-operation. In this study, the problems about the taken informed consent pre-operation being legal neçessity were pointed out. The treatment manner in such cases was suggested.Key Words: Informed consent, medical malpractice, forensic science
Keywords: informed consent; medical malpractice; forensic science